Use of Raman spectroscopy for determination of the effect of herbicides on carotenoid content in Chenopodium album and Abutilon theophrasti leaves - Vranješ, Filip; Pećinar, Ilinka; Lević, Steva; Vrbničanin, Sava; Božić, Dragana (Acta herbologica, 2020)
Raman spectroscopy has so far proved to be a suitable method for the analysis of carotenoids in a wide range of plant samples. This study aimed to determine whether the influence of mesotrione on changes in carotenoid content in the leaves of treated weed species, Chenopodium album, and Abutilon theophrasti can be detected using Raman spectroscopy. When the plants reached the targeted growth stage (C. album: 4 leaves, and A. theophrasti: 2 leaves), the product Skaut (a.i. mesotrione 480 g l-1, SC) was applied in an amount of 120 g a.i. ha-1 in the tank mix with adjuvant Alteox wet 40 (a.i. mineral oil (500 g l-1) + polyoxy alcohol (500 g l-1)) in the amount of 1 l ha-1. Leaf analysis, using Raman spectroscopy, was performed four times: the 1st, 2nd, 3rd, and 7th day after the mesotrione application. In the obtained Raman spectra, the intensity of the bands at positions 1007, 1155, and 1522 cm-1 in untreated and treated plants was analysed to determine the relative carotenoid content. The obtained results showed that with C. album changes in the relative carotenoid content in the leaves of treated plants could be detected as early as 3 days after mesotrione application compared to the leaves of untreated plants of the same age. Furthermore, a statistically significant difference was found on the same parameter in leaves of A. theophrasti later compared to C. album, on the 7th day after mesotrione application. This study confirmed that Raman spectroscopy can be used as an adequate method for the rapid detection of the effect of herbicides on the content of carotenoids in the leaves of treated weed species.